Barghash : sultan of Zanzibar (Encyclopaedia Britannica, 2024)
Barghash was the sultan of Zanzibar (1870–88), a shrewd and ambitious ruler, who, for most of his reign, looked to Britain for protection and assistance but eventually saw his domains divided between Germany and his former protector. Although not the first heir to the throne of his father, Saʿīd
Keywords: Biographies -- Zanzibar

توفي قبل نحو 97 عامًا: السيد خالد بن برغش وجزيرة المنفى (سانت هيلانة) - الجهورية, أحلام بنت حمود (صحيفة أثير الإلكترونية, 2021)
المنفى أدبيا يختزل ثيمة الاستبعاد والخروج والهجرة القسرية والغربة والفراق، والنفي كحدث تاريخي يختزل في داخله فترة تاريخية بشخوصها وظروفها المختلف…
Keywords: Biographies -- Zanzibar